Several New Substituted Azetidinonyl and Thiazolidinonyl Quinazolon 4 3H Ones as their Anti Inflammatory Activities - Bhati, Sudhir Kumar (International Journal of Pharmaceutical & Biological Archive, 2013)
Several New Substituted Azetidinonyl and Thiazolidinonyl Quinazolon 4 3H Ones as their Anti Inflammatory Activities